2014
DOI: 10.1007/s11910-014-0503-3
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Apnea and Stroke

Abstract: Clinical evidence has established that sleep apnea is a risk factor for stroke. Patients with stroke have a high prevalence of sleep apnea that may have preceded or developed as a result of the stroke. Well-established concurrent stroke risk factors for stroke like hypertension and atrial fibrillation respond favorably to the successful treatment of sleep apnea. The gold standard diagnosis of sleep apnea is obtained in the sleep laboratory, but unattended polysomnography is gaining acceptance. Positive airway … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 54 publications
(39 reference statements)
0
13
0
Order By: Relevance
“…NOD was observed in 16.8% in our study, which was lower than the reported prevalence of sleep apnea after stroke using polysomnography. 6,7,9,23 In addition, we excluded patients treated with oxygen to minimize bias. This could have affected the lower rate of sleep-disordered breathing in our patients, despite the absolute numbers being small.…”
Section: Strokementioning
confidence: 99%
See 1 more Smart Citation
“…NOD was observed in 16.8% in our study, which was lower than the reported prevalence of sleep apnea after stroke using polysomnography. 6,7,9,23 In addition, we excluded patients treated with oxygen to minimize bias. This could have affected the lower rate of sleep-disordered breathing in our patients, despite the absolute numbers being small.…”
Section: Strokementioning
confidence: 99%
“…5,6 Specifically, sleep-disordered breathing may be associated with the development of WUS. Nocturnal hypoxia may trigger ischemia [6][7][8][9] or may increase the risk of ischemic event probably mediated by hypertension. Previous reports have suggested the possible association between WUS and sleep-disordered breathing.…”
mentioning
confidence: 99%
“…39 Obstructive sleep apnea can lead to reductions in cerebral blood flow and impaired cerebral autoregulation, possibly damaging the small vessels in the brain.…”
Section: Vascular Mechanisms Between Osa and Strokementioning
confidence: 99%
“…In addition, the benefits and timing of CPAP therapy after an acute stroke are not established. However, OSA patients at increased stroke risk or those who had a stroke should be risk-stratified, evaluated, and encouraged to use CPAP regularly as part of standard stroke care, 39 and because blacks and Hispanics have a history of poor CPAP compliance, culturally-tailored interventions are needed to increase CPAP compliance to reduce stroke events. 64 …”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…Accumulating evidence indicates that sleep abnormalities are associated with many adverse health outcomes, such as metabolic syndrome [9], hypothyroid [10], obesity [11], especially CVD and stroke [12][13][14][15]. In addition, in the hospital groups, some previous studies have showed that obstructive sleep apnea (OSA) was associated with Hhcy.…”
Section: Introductionmentioning
confidence: 99%